2011
DOI: 10.1186/1475-2891-10-67
|View full text |Cite
|
Sign up to set email alerts
|

Acute reduction of serum 8-iso-PGF2-alpha and advanced oxidation protein products in vivo by a polyphenol-rich beverage; a pilot clinical study with phytochemical and in vitro antioxidant characterization

Abstract: BackgroundMeasuring the effects of the acute intake of natural products on human biomarker concentrations, such as those related to oxidation and inflammation, can be an advantageous strategy for early clinical research on an ingredient or product.Methods31 total healthy subjects were randomized in a double-blinded, placebo-controlled, acute pilot study with post-hoc subgroup analysis on 20 of the subjects. The study examined the effects of a single dose of a polyphenol-rich beverage (PRB), commercially market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
(56 reference statements)
1
18
0
2
Order By: Relevance
“…However, in the study on effect of diet-induced reduction in oxidative stress it has been showed that F 2 -isoprostane level was well correlated with advanced oxidation protein products [69]. In addition, one should be cautious if generalizing this study’s finding to males, obese individuals, and populations with serious obesity-related diseases, such as type 2 diabetes or hyperlipidemias.…”
Section: Discussionmentioning
confidence: 85%
“…However, in the study on effect of diet-induced reduction in oxidative stress it has been showed that F 2 -isoprostane level was well correlated with advanced oxidation protein products [69]. In addition, one should be cautious if generalizing this study’s finding to males, obese individuals, and populations with serious obesity-related diseases, such as type 2 diabetes or hyperlipidemias.…”
Section: Discussionmentioning
confidence: 85%
“…A reduction of oxidative stress biomarkers such as 8-isoprostaglandin F2a has been reported after consumption of blonde orange juice (44) or other polyphenol-rich beverages (45). Free radicals and reactive oxygen and nitrogen species may react with proteins and lead to the conversion of amino acid residues into carbonyl groups.…”
Section: Discussionmentioning
confidence: 98%
“…Through numerous animal and clinical experiments it has been assumed that most of the beneficial effects of polyphenols are related to their antioxidant properties. Polyphenols have been shown to be effective antioxidants in a wide range of chemical oxidation systems, as demonstrated by their ability to scavenge reactive oxygen (ROS) or nitrogen species such as hydroxyl, peroxyl, superoxide, hydrogen peroxide, or singlet oxygen (Ross and Kasum ; Nemzer and others ; Sandoval‐Acuna and others ). These radicals are involved in oxidative stress and may play crucial roles in the development of tumors, atherosclerosis, diabetes, Alzheimer's disease, Parkinson's disease, or in the entire ageing process (Mladenka and others ; Nemzer and others ).…”
Section: General Health‐promoting Effectsmentioning
confidence: 99%
“…However, excessive inflammation can be dangerous and may lead to pathological changes in cells. Inflammatory abnormalities are a large group of disorders that are associated with numerous diseases such as cancer, atherosclerosis, erectile dysfunction, arthritis, obesity, or ischemic heart disease (Nemzer and others ; Raza and others ). In a significant number of studies, in vitro and in vivo , the effect of polyphenols on expression and activity of pro‐inflammatory factors have been demonstrated.…”
Section: Effects Against Specific Health Threatsmentioning
confidence: 99%
See 1 more Smart Citation